(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
The terminal part of large intestine and Moola of Pureeshavastrotas is known as Guda. It is one of the Bahirmukhstrotas and also considered as one of the Karmendriyan. Charak has mentioned that Guda is one of the Koshtangas. Guda is defined as the passage through which excretion of faeces takes place and is located in the pelvic region and Charaka recognized two parts in it i.e., Uttara guda and Adhara Guda. It is one among nine Bahirmukhasrotas located in pelvic region. It is continuation of large intestines. Embryologically it is derived from Matrujabhava. Total length of Guda is 4½ angula. There are 3 sphincter situated inside the Guda placed one above the other at a distance of 1½ angula from each other and are named as Pravahini, Visarjini and Samvarni. Pureeshdhara Kala is related to Guda and it is Moola of Pureeshvahasrotas and also is Sadhyopranhara Marma. The diseases related to Guda are Arsha, Bhagandara, Gudavidradhi, Sannirudh Guda, Gudabhransha. Objective of the study are comprehensive literary review of Guda Sharira with correlation of anatomical features described in Ayurveda to contemporary science. Data related to Guda Sharira and diseases were collected from various classics and specimen of rectum and anal canal from cadaveric study.